TRANSFORMATIVE EXPERIENCE: CONTRIBUTION TO THE UNIEVANGÉLICA CIDADÃ ITINERANTE INSTITUTIONAL PROJECT – HEALTH EDUCATION AND IMMUNIZATION (CIPEEX, 2025)
This experience report describes participation in the UniEVANGÉLICA Cidadã Itinerante (UniEVANGÉLICA Traveling Citizen) Institutional Project, which aimed to increase vaccination coverage and raise community awareness about dengue prevention. In partnership with the Anápolis Health Department, the project integrated immunization and educational activities focused on children and university students. The objective was to assess the impact of health education activities on community awareness and participant engagement. The methodology involved the participation of academic leagues that organized technical lectures for university students and interactive presentations for children, using teaching materials adapted to different age groups. During the three-day event, 70 children and 50 university students actively participated. The results showed significant engagement, with a clear understanding of how to prevent dengue and the crucial role of vaccination. The final considerations highlight the effectiveness of integrating education and vaccination, demonstrating the positive impact on public health and the training of future professionals in the field.
Keywords: League; Dengue; Immunization; Health